Treponema pallidum (Syphilis) Antigen TpF1 Induces Activation of Macrophages and Accelerates P2X7R-Induced NLRP3-Dependent Release of IL-1β - Lu, Dong-Ping; Jia, Jie; Wei, Shao-Feng; Zhang, Wei-Lian; Liang, Rui; Liu, Ting; Yang, Wen-Zhi; Li, Bing-Yan; Zhang, Rong; Wang, Fen (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2022)
Background: Syphilis is a chronic infectious disease caused by Treponema pallidum (Tp) infection, which causes local inflammation in the host. TpF1 is an oligomeric protein expressed by the Tp-infected host that can induce the host immune response. There are few studies regarding the role of TpF1 in macrophage activation and the subsequent release of cytokines. Objective: The objective of this study is to elucidate the effects of TpF1 on the pathological process of Syphilis. In addition, we explored how purinergic 2X7 (P2X7R) induced NOD-like receptor family protein 3 (NLRP3) -dependent release of interleukin-1β (IL-1β) and the underlying mechanisms. Methods: We explored the influence of TpF1 on cytokine release by macrophages using qRT-PCR and ELISA. The specific phenotype of activated macrophages was determined by flow cytometry. Results: TpF1 was able to activate macrophages and induce the M1 macrophage phenotype. Moreover, TpF1 activated the NLRP3 inflammasome in macrophages, which was mediated by P2X7R. Conclusion: The Tp-induced protein TpF1 is able to induce macrophage activation and P2X7R-induced NLRP3-dependent release of IL-1β. Our findings provide a theoretical basis for clarifying the clinical symptoms and pathogenesis of syphilis.
Keywords: macrophage